Vectorial Kinetic Relaxation Model with Central Velocity. Application to Implicit Relaxations Schemes (Communications in Computational Physics, 2020)
We apply flux vector splitting (FVS) strategy to the implicit kinetic schemesfor hyperbolic systems. It enables to increase the accuracy of the method compared toclassical kinetic schemes while still using large time steps compared to the characteristic speeds of the problem. The method also allows to tackle multi-scale problems, suchas the low Mach number limit, for which wave speeds with large ratio are involved. Wepresent several possible kinetic relaxation schemes based on FVS and compare themon one-dimensional test-cases. We discuss stability issues for this kind of method.
Keywords: Implicit scheme; kinetic; flux vector splitting; Euler equation; relaxation.